Soaking Period of Cooked Blood Cockle (Anadara granosa) Meat in Alginate Solution to Cadmium Content Reduction - Al Chusein, Achid Furqon; Ibrahim, Ratna (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2012)
Some blood cockles in the West Banjir Kanal river estuary in Semarang have been contaminated  by some heavy metal that exceeds the level of Indonesian National Standard requirement. The research aimed to find out the effect of different soaking period of cooked blood cockle (Anadara granosa) meat in 4.0%  alginate solution to the cadmium content reduction, moisture content, ash content, pH and organoleptic  values of the product. The experimental design used was completely randomized design with three  treatments, namely the soaking period of cooked blood cockle meat in 4.0% alginate solution for 10 minutes, 20 minutes, 30 minutes and control (without soaking). Each of the treatment was done in triplicate. The results  showed that the different soaking period of cooked blood cockle meat in 4.0% alginate solution (for 10 minutes, 20 minutes, 30 minutes) resulted in highly significant reduction of cadmium content which was from 1.588 mg/kg (control) to 0.463 mg/kg (the lowest) after 30 minutes soaking period. The longer the  soaking   period of cooked blood cockle meat in 4.0% alginate solution the lower the cadmium content. The soaking period of cooked blood cockle meat in 4.0% alginate solution for 30 minutes was the best soaking period because it could reduce the content of cadmium up to 0.463 mg/kg and the organoleptic value was 7.89 which met the quality requirements of cooked blood cockle meat according to SNI.  Key words: Cooked blood cockle meat, alginate, cadmium, pH, quality